Growing up Without a Father: Social Support in Emerging Adulthood Experiencing Fatherlessness - Siti Faedattusyahadah; Sarita Candra Merida; Tugimin Supriyadi (Inovan Publisher, 2026)
This study was motivated by the importance of social support for individuals in emerging adulthood who have lost a father figure due to their parents’ divorce. The study aims to describe social support among individuals in emerging adulthood who have lost a father figure due to their parents’ divorce. This study employed a descriptive quantitative approach, involving 100 respondents aged 18–29 years who were selected using purposive sampling. Data collection was conducted using a social support scale comprising emotional support, instrumental support, informational support and appreciative support. The data were analyzed using categorization techniques. The results indicate that the majority of respondents had high levels of social support. Informational support was the most frequently received form of social support among respondents, followed by emotional support, appreciative support, and instrumental support. The results indicate that individuals in emerging adulthood who have lost their fathers due to their parents’ divorce continue to receive various forms of support from their social environment. Social support serves as an important resource in helping individuals cope with the various developmental challenges of emerging adulthood.